Prescribing patterns of rural family physicians: a study in Kermanshah Province, Iran - Fariba Ahmadi; Ehsan Zarei (BMC, 2017)
Abstract Background The inappropriate use of drugs due to irrational prescriptions is a common problem in Iran, but there is little evidence of prescription patterns in rural family physicians. This study aimed to explore the prescribing pattern and rational drug use indicators for family physicians using Index of Rational Drug Prescribing (IRDP) in Kermanshah Province, Iran. Methods In this retrospective study, 352,399 prescriptions from 184 family physicians in 103 primary health care (PHC) centers were examined. As stated, an analysis was done for rational use indicators suggested by World Health Organization (WHO): e.g., the percentage of prescriptions containing antibiotics, injections, and those prescribed by a generic name and from a national essential medicine list, plus the average number of drugs per prescription; these factors were all taken into account. Rational drug use was studied with the IRDP. Results The average number of drugs per prescription was 3.14 (± 1.2) and the average cost per prescription was 116,740 IRR (USD 3.6). Around 19% of prescriptions had more than four drugs, while the percentage of prescriptions involving antibiotics and injections was 52.1% and 24.4%, respectively. There was 95.1% drugs prescribed by their generic name and 95.9% were retrieved from the essential drugs list. The value of the IRDP was 3.70 out of 5. Conclusion The findings of this study showed that some degree of irrational drug prescribing exists among family physicians, especially in terms of injections, antibiotics, and polypharmacy. It is recommended that there be continuing education programs for physicians regarding rational prescribing for different kinds of medical indications. Clinical practice guidelines should also assist with the rational use of medicine.